Achieving Continuous Self‐Powered Energy Conversion‐Storage‐Supply Integrated System Based on Carbon Felt - Ji Peiyuan; Li Qianying; Zhang Xuemei; Hu Yawen; Han Xiangyu; Zhang Dazhi; Hu Chenguo; Xi Yi (Advanced Science, 2023)
Abstract Efficient harvesting and storage of dispersed irregular energy from the environment are crucial to the demand for the distributed devices of the Internet of Things (IoTs). Here, a carbon felt (CF)‐based energy conversion‐storage‐supply integrated system (CECIS) that contains a CF‐based solid‐state supercapacitor (CSSC) and a CF‐based triboelectric nanogenerator (C‐TENG) is presented, which is capable of simultaneously energy storage and conversion. The simple treated CF not only delivers a maximal specific capacitance of 402.4 F g−1 but also prominent supercapacitor characteristics with fast charge and slow discharge, enabling 38 LEDs successfully lightened for more than 900 s after a wireless charging time of only 2 s. With the original CF as the sensing layer, buffer layer, and current collector of C‐TENG, the maximal power of 91.5 mW is attained. The CECIS shows a competitive output performance. The time ratio of the duration of supply energy to the harvesting and storage reaches 9.6:1, meaning that it is competent for the continuous energy application when the effective working time of C‐TENG is longer than one‐tenth of the whole day. This study not only highlights the great potential of CECIS in sustainable energy harvesting and storage but also lays the foundation for the ultimate realization of IoTs.